The Effect of Problem-Based Learning (PBL) Assisted by TPACK on Elementary School Mathematics Learning Outcomes - Asih Mardati; Sinta Amalia Rifqoh; Yeyen Febrilia (Jurnal Inovasi Matematika, 2026)
Mathematics learning in elementary schools is one of the lessons developed in the student environment. Students in class III usually have difficulty in understanding the concept of division. The purpose of this research is to find out whether there is an influence on the application of the problem-based learning (PBL) model assisted by TPACK significantly affected the mathematics learning outcomes of division material in class III students at SD Muhammadiyah Pajangan 2. This research is quantitave with experimental research. The design of this research is quasi-experiment with nonequivalent control group design. The data collected by pre-test and post-test. This research uses 2 classes such as control class and experimental class. The validation results in this study used product moment. The validation results is , so 10 questions of pre-test and post-test are valid. The experimental class that was given treatment using the PBL model showed significant results when viewed from the standards on the subject 57.9, this is classified as quite effective. The control class itself which was given treatment using the conventional learning model showed poor results, seen from the gain score of 28.7. Problem-based learning (PBL) assisted by TPACK can be concluded to be applicable in the learning process of third-grade division mathematics. Thus, the contribution of this research can assist teachers in implementing a learning model that supports students' understanding of division material.